2018
DOI: 10.1111/jfb.13794
|View full text |Cite
|
Sign up to set email alerts
|

Fin healing and regeneration in sturgeon

Abstract: Pectoral fin healing in fin spines and rays were examined in juvenile Atlantic sturgeon Acipenser oxyrinchus oxyrinchus following three different sampling techniques (n = 8-9 fish per treatment): entire leading fin spine removed, a 1-2 cm portion removed near the point of articulation, or a 1-2 cm portion removed from a secondary fin ray. Also, to determine whether antibiotic treatment influences healing, an additional group of fish (n = 8) was not given an injection of an oxytetracycline (OTC)-based antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In addition, Allen et al. (2018a) confirmed that the complete regeneration of the pectoral fin ray in juvenile Atlantic Sturgeon was achieved after 12 months of healing. With specific reference to Lake Sturgeon (the focus of our study), a recent mark–recapture study from the Winnipeg River (wherein all juvenile Lake Sturgeon captured had fin rays removed for aging) produced annual survival estimates of 0.99 (McDougall et al.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Allen et al. (2018a) confirmed that the complete regeneration of the pectoral fin ray in juvenile Atlantic Sturgeon was achieved after 12 months of healing. With specific reference to Lake Sturgeon (the focus of our study), a recent mark–recapture study from the Winnipeg River (wherein all juvenile Lake Sturgeon captured had fin rays removed for aging) produced annual survival estimates of 0.99 (McDougall et al.…”
Section: Discussionmentioning
confidence: 94%
“…The dermal fin folds are useful during swimming, but due to their fine structure, they can get easily injured, therefore, the capacity to regenerate them has clear adaptive value. Exoskeletal regeneration has been described in many Actinopterygian species, (e.g., sturgeon (Acipenser oxyrinchus) [35], short-lived killifish (Nothobranchius furzeri) [36], sailfin molly (Poecilia latipinna) [37], mexican cavefish (Astyanax mexicanus) [38], medaka (Oryzias latipes) [39], loach (Paramisgurnus dabryanu) [40] and several others [41]), suggesting that this is an ancestral trait of ray-finned fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, telemetry is often an inviable option when working with endangered species, as capture, surgery, and transmitter application may be harmful (Nielsen 1998;Godfrey et al 2003). Trace elements have been demonstrated to be a useful technique for identifying life history traits in sturgeons (Allen et al 2009(Allen et al , 2018a.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques were found to be useful when identifying the spawning location, age determination, and growth of A. oxyrinchus oxyrinchus (Atlantic Sturgeon) (Stevenson and Secor 2000;Balazik et al 2012) and in A. brevirostrum (Shortnose Sturgeon) (Altenritter et al 2015). Strontium (Sr) isotopes, are also used to identify natal spawning areas of freshwater fishes (Hobbs et al 2007;Hobbs et al 2010), and contemporary studies have used them to distinguish freshwater movements of juvenile Gulf Sturgeon in the Choctawhatchee River System (Allen et al 2018a). Trace element and Sr isotopes analysis are potentially useful for other river systems occupied by Gulf Sturgeon, such as the Pearl River System in Louisiana and Mississippi where little is known of movements and habitat use of juveniles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation